Profile of Eyelid Tumours: Histopathological Examination and Relative Frequency At A Tertiary Centre In North-West Rajasthan - Mahendra Kumar Jangir; Anju Kochar; Nabab Ali Khan; Meenu Jaju (Delhi Journal of Ophthalmology)
Purpose:- To analyze the demography and relative frequency and to compare the clinical diagnosis with histopathological diagnosis of eyelid tumours at a tertiary care centre in North-West Rajasthan. Methods:- Retrospective data of patients with eyelid tumours from June 2012 to June 2014 and prospective data of patients from July 2014 to December 2016 were analyzed. Data were collected and stratified based on age, gender, type and subtype, location of tumour and histopathological diagnosis. Results:- A total of 125 patients were evaluated, of which, 54.4% (68) were male and 45.6% (57) were female. The mean age of the patients was 37.28+21.75 years. Out of the total cases, 108 (86.4%) cases were benign and 17 (13.60%) were malignant eyelid tumours. The most common benign tumour included epidermal cyst (21.3%), demoid cyst (13.89%), intradermal naevus (12.03%) and haemangioma (12.03%). The most frequent malignant tumours included sebaceous gland carcinoma (47%), basal cell carcinoma (29%) and squamous cell carcinoma (24%). Conclusion:- Epidermal cyst was the most common benign tumour followed by demoid cyst, intradermal naevus and haemangioma and sebaceous gland carcinoma was the most common malignant tumour, followed by basal and squamous cell carcinoma.